Oreocharis caobangensis (Gesneriaceae), a new species from Cao Bang Province, northern Vietnam - Do, Truong Van; Wei, Yi-Gang; Wen, Fang (Phytotaxa, 2017)
A new species of Oreocharis (Gesneriaceae) from Cao Bang province, northern Vietnam is described and illustrated. The new species, Oreocharis caobangensis, is most similar to O. lungshengensis, but it can be easily distinguished from the latter by its petioles densely brownish villous, lateral veins 6–8 pair on each leaf blade, bracts smaller (1.5–2 mm long), corolla outside pubescent and pistil glabrous, 18–20 mm long.